In silico Studies of Plant-Derived Bioactive Compounds of Wedelia Species - Rani, Nidhi; Dahiya, Randhir S.; Kumar, Praveen (Anti-Infective Agents, 2022)
Background: In India, several types of plants have been researched for the treatment of various ailments. Wedelia species, belonging to the Asteraceae family, is one of the wonder plants that has been utilised in Unani, Ayurvedic, and Homeopathic treatment for a long time. Objective: The components of Wedelia species were investigated in order to create novel powerful anti-fungal drugs with low toxicity and high efficacy followed by high bioavailability. Methods: Molergo Virtual Docker was used to test the chemical components of the plant for antifungal potential against the enzyme 14-demethylase. Results: According to the findings, about fifteen compounds were identified as promising compounds with a high dock score and number of interactions. Conclusion: These compounds can further be isolated and worked upon for future research.
Keywords: anti fungal drugs